The role of transformation narratives in desistance among released lifers - Liem, Marieke (Criminal justice and behavior, 2014)
Research on desistance emphasizes the importance of the transformation narrative, in which the individual has replaced his old, criminal self with a new, law-abiding self. Key elements of the transformation narrative are generative motivations, the core self, and a sense of agency. Thus far, it is not known what role these elements play in desistance among released lifers. To fill this caveat, we conducted in-depth life interviews with 67 individuals who had served a life sentence. Almost all interviewees presented a transformation narrative that included a good core self and generative motivations, including those who persisted in criminal behavior. We found that individual agency was a key factor distinguishing the paroled lifers from the re-incarcerated lifers. Findings suggest that rather than learning to present a transformation narrative focused on reflecting a good core self and generative motivations, (post-)prison programs should focus on restoring agency to ensure successful re-entry.